2008
DOI: 10.3748/wjg.14.5880
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus enhances incidence of idiopathic pulmonary fibrosis

Abstract: AIM: To investigate the cumulative development incidence and predictive factors for idiopathic pulmonary fibrosis in hepatitis C virus (HCV) positive patients. METHODS: We studied 6150 HCV infected patients who were between 40-70 years old (HCV-group). Another 2050 patients with hepatitis B virus (HBV) were selected as control (HBV-group). The mean observation period was 8.0 ± 5.9 years in HCV-group and 6.3 ± 5.5 years in HBV-group. The primary goal is the development of idiopathic pulmonary fibrosis (IPF) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 34 publications
0
47
0
Order By: Relevance
“…A Japanese case-control study relying on self-reported diagnosis of HCV infection also did not find a significant association between HCV infection and the risk of developing IPF [57]. More recently, among more than 6,000 Japanese HCVinfected patients, 15 developed IPF during a mean followup of 8 years, whereas IPF was not diagnosed in any of more than 2,000 hepatitis B virus-infected patients followed for a mean of 6.3 years [58]. In particular, HCV patients aged ≥55 years, with ≥20 pack-years of smoking and who had liver cirrhosis were at increased risk of developing IPF.…”
Section: Hepatitis C Virusmentioning
confidence: 89%
“…A Japanese case-control study relying on self-reported diagnosis of HCV infection also did not find a significant association between HCV infection and the risk of developing IPF [57]. More recently, among more than 6,000 Japanese HCVinfected patients, 15 developed IPF during a mean followup of 8 years, whereas IPF was not diagnosed in any of more than 2,000 hepatitis B virus-infected patients followed for a mean of 6.3 years [58]. In particular, HCV patients aged ≥55 years, with ≥20 pack-years of smoking and who had liver cirrhosis were at increased risk of developing IPF.…”
Section: Hepatitis C Virusmentioning
confidence: 89%
“…In a Japanese study, which contained 66 subjects with IPF and 9646 controls, UEDA et al [8] found that 28.8% of IPF subjects, but only 3.66% of controls, had evidence of prior HCV infection. ARASE et al [9] addressed the same question from the opposite direction. They studied a cohort of 6150 patients with HCV and a cohort of 2050 patients with Hepatitis B (HBV).…”
Section: Infection and The Pathogenesis Of Ipfmentioning
confidence: 93%
“…Major study findings Comment HCV 28% of an IPF cohort had evidence of prior HCV compared with 3.6% of controls [8] The lack of a coherent signal across studies suggests that HCV is unlikely to be an important trigger for the development of IPF Incidence of IPF higher in cohort of HCV positive individuals compared to cohort with HBV [9] No association between IPF and HCV [10] Association of HCV with a range of non-fibrotic respiratory conditions [ subjects when compared to controls [15][16][17]25]. Whilst EBV has been the most frequently studied of the HHVs, TANG et al [18] looked more broadly at a range of HHV family members and found evidence of past infection with at least one HHV in 97% of patients with IPF compared to only 36% of healthy controls.…”
Section: Virusmentioning
confidence: 99%
“…A major concern, that has not been fully addressed, is the possibility that enhanced levels of some of these biomarkers can be found in IIPs as well as in malignancies, while these diseases may very well coincide. For example, an increased incidence of IPF has been reported in patients with hepatitis C virus (HCV) infection [73][74]. Arase et al reported increased levels of KL-6 one year before clinical onset of IPF in HCV patients [75].…”
Section: Discussionmentioning
confidence: 99%